Evaluation of Methadone Treatment in Malaysia: Findings from the Malaysian Methadone Treatment Outcome Study (MyTOS). (28th January 2018) - Ali, Norsiah; Aziz, Salina Abd; Nordin, Salmah; Mi, Norliza Che; Abdullah, Norni; Paranthaman, V.; Mahmud, Maimunah; Yee, Anne; Danaee, Mahmoud
ABSTRACT: Background : Opioid misuse and dependence is a global issue with a huge negative impact. In Malaysia, heroin is still the main illicit drug used, and methadone maintenance treatment (MMT) has been used since 2005. Objective : To evaluate the effectiveness of MMT. Methods : This was a cross-sectional study conducted in 103 treatment centers between October and December 2014 using a set of standard questionnaires. Data were analyzed using SPSS Statistics 20. Results : There were 3254 respondents (93.6% response rate); of these 17.5% ( n = 570) transferred to another treatment center, 8.6% ( n = 280) died, 29.2% ( n = 950) defaulted, and 7.6% ( n = 247) were terminated for various reasons. Hence, 1233 (37%) respondents' baseline and follow-up data were further analyzed. Respondents had a mean age of 39.2 years old and were mainly male, Malay, Muslim, married (51.1%, n = 617), and currently employed. Few showed viral seroconversion after they started MMT (HIV: 0.5%, n = 6; Hepatitis B: 0.3%, n = 4; Hepatitis C: 2.7%, n = 29). There were significant reductions in opioid use, HIV risk-taking score ( p < 0.01), social functioning ( p < 0.01), crime ( p < 0.01), and health ( p < 0.01). However, there were significant improvements in quality of life in the physical, psychological, social, and environmental domains. Factors associated with change were being married, employed, consuming alcohol, and high criminality at baseline. Lower methadone dosage was significantly associated with improvements in the physical, psychological, and environmental domains. Conclusion/Importance : The MMT program was found to be successful; hence, it should be expanded.